Lactobacillus plantarum CCFM1180 attenuates obesity induced by estrogen deficiency by activating estrogen receptor alpha in abdominal adipose tissue and regulating gut microbiota-derived metabolites - Qian Chen; Chunxia Mei; Min Guo; Botao Wang; Haiqin Chen; Jianxin Zhao; Gang Wang; Wei Chen (Food Science and Human Wellness)
Lipid metabolism disorders commonly occur during menopause. Estrogen deficiency has been shown to lead to excessive energy intake and abnormal lipid metabolism in ovariectomized rats, resulting in obesity. Probiotics exhibit anti-obesity properties, and their underlying mechanism has been widely reported. In this study, we demonstrated the metabolic benefits of Lactobacillus plantarum CCFM1180 in suppressing appetite, controlling body weight, correcting obesity-induced abnormalities, enhancing liver lipid metabolism, and protecting liver function in estrogen-deficient rats. The mechanisms associated with the anti-obesity and antidyslipidemia effects of CCFM1180 on estrogen-deficient rats were clarified. The results showed that CCFM1180 dramatically reduced food intake by activating the expression of estrogen receptor alpha (ERα) and increasing the level of leptin in abdominal adipose tissue. These changes, combined with the increased butyrate concentration and recovered bile acid structure, helped enhance lipid metabolism. Additionally, CCFM1180 treatment was found to be safer than exogenous estrogen supplementation. Thus, L. plantarum CCFM1180 could be considered a new therapeutic strategy for preventing and alleviating menopausal lipid abnormalities.